Rationale and design for Healthy Hearts in Manufacturing (HHM): A pragmatic single-arm hybrid effectiveness-implementation study for hypertension management and tobacco cessation - Hanzi Jiang; Yao Tian; Jennifer Bannon; Amy E. Krefman; Lawrence C. An; Dustin D. French; Claude R. Maechling; Jane Holl; Richard Chagnon; Theresa L. Walunas; Christopher Burch; Anthony Musci; et al. (Contemporary Clinical Trials Communications)
Background: Heart disease is the leading cause of mortality in the United States and contributes more than $320 billion annually in health care costs and lost productivity. Manufacturing employment is associated with higher rates of hypertension and smoking. Many large manufacturers provide health services to employees and their family members through worksite health centers (WHCs). Several quality improvement interventions for hypertension and tobacco cessation have shown to be effective in community-based primary care sites. The Healthy Hearts in Manufacturing (HHM) study aims to implement and test these interventions in WHCs. Methods: Two organizations that operate WHCs at manufacturing sites volunteered to participate in the 58-month HHM research study. The HHM intervention involves monthly coaching to assist WHCs with implementing evidence-based strategies for hypertension management and tobacco cessation advocated by the Million Hearts initiative and the U.S. Preventive Services Task Force. A pragmatic, Type II hybrid effectiveness-implementation study design is used to evaluate HHM. The approach is inspired by the stepped-wedge cluster-randomized trial to assess intervention effectiveness. We will conduct interviews to identify facilitators and barriers to implementation and budget impact analysis to estimate the financial impact of the HMM interventions and the potential healthcare savings to companies and Medicare. Results: Twelve WHCs were randomly selected to enroll in HHM. The WHCs are in nine states and provide primary care services for employees and family members of four manufacturing companies. Baseline patient smoking rates ranged from 13 % to 59 % across WHCs. The percentage of patients with blood pressure of 140/90 or greater ranged from 7 % to 56 % across WHCs. Conclusion: This exploratory five-year research study will identify facilitators and barriers to implementing the HHM interventions in WHCs, evaluate the effectiveness of hypertension management and use of tobacco screening and cessation, and provide evidence of HHM's potential cost-effectiveness for employers and Medicare.